2017
DOI: 10.1002/oby.21723
|View full text |Cite
|
Sign up to set email alerts
|

The impact of telephonic wellness coaching on weight loss: A “Natural Experiments for Translation in Diabetes (NEXTD)” study

Abstract: Objective: To evaluate the impact of a population-based telephonic wellness coaching program on weight loss. Methods: Individual-level segmented regression analysis of interrupted time series data comparing the BMI trajectories in the 12 months before versus the 12 months after initiating coaching among a cohort of Kaiser Permanente Northern California members (n 5 954) participating in The Permanente Medical Group Wellness Coaching program in 2011. The control group was a 20:1 propensity-score matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…electronic health records, web-based and mobile-accessible platforms, text messaging) can enable health behavior change and improve adherence over scheduled in-person weight management interventions [30]. In fact, remotely-delivered behavioral health coaching has been shown to be an effective tool in the management of a wide range of health conditions, including obesity [34], and is often a service provided by health plans [35]. Growing evidence supports remote delivery of behavioral interventions as efficient and potentially more accessible for young women [36,37], particularly in the postpartum period when attrition rates are highest [38].…”
Section: Discussionmentioning
confidence: 99%
“…electronic health records, web-based and mobile-accessible platforms, text messaging) can enable health behavior change and improve adherence over scheduled in-person weight management interventions [30]. In fact, remotely-delivered behavioral health coaching has been shown to be an effective tool in the management of a wide range of health conditions, including obesity [34], and is often a service provided by health plans [35]. Growing evidence supports remote delivery of behavioral interventions as efficient and potentially more accessible for young women [36,37], particularly in the postpartum period when attrition rates are highest [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our results report the outcomes of an insurer-based coaching program, and are one of the few such studies that describe results outside the clinical trial setting. In contrast to telephone coaching in clinical trials which focus on one behavioral goal, coaching programs outside the trial setting may support multiple behaviors ( O'Hara et al, 2012 ; Adams et al, 2013 ; Schmittdiel et al, 2017 ). In our program, we found that most participants' primary goal was weight loss, although improving general health was another common goal.…”
Section: Discussionmentioning
confidence: 99%
“…One evaluation studied a government-sponsored health coaching program in Australia, which led to improvements in weight, exercise, and diet at 6 months ( O'Hara et al, 2012 ). U.S. insurer-sponsored wellness coaching programs showed coaching's positive impacts on body mass index (BMI) and smoking cessation ( Adams et al, 2013 ; Schmittdiel et al, 2017 ; Boccio et al, 2017 ). A wellness coaching program in an insured population produced small weight losses ( Tao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…NEXT-D2 builds upon activities of the original NEXT-D Network of five centers funded by the Centers for Disease Control and Prevention (CDC) and the National Institutes of Health (NIH) that launched in 2010, called "Natural Experiments and Effectiveness Studies to Identify the Best Policy and System Level Practices to Prevent Diabetes and Its Complications" [19]. Several NEXT-D reports have described the impact of population-targeted policies (e.g., electronic health record screening decision prompts, lifestyle modification programs, targeted copayment reductions for diabetes care, high deductible health plans) on preventive behaviors and diabetes outcomes, quantity and quality of care, morbidity and costs, and unintended consequences of these policies [9,[23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Description Of the Networkmentioning
confidence: 99%